Captive Rearing Experiments Confirm Song Development without Learning in a Tracheophone Suboscine Bird - Touchton,JM; Seddon,N; Tobias,JA (PLOS One, 2014)
The origin of vocal learning in animals has long been the subject of debate, but progress has been limited by uncertainty regarding the distribution of learning mechanisms across the tree of life, even for model systems such as birdsong. In particular, the importance of learning is well known in oscine songbirds, but disputed in suboscines. Members of this diverse group (∼1150 species) are generally assumed not to learn their songs, but empirical evidence is scarce, with previous studies restricted to the bronchophone (non-tracheophone) clade. Here, we conduct the first experimental study of song development in a tracheophone suboscine bird by rearing spotted antbird (Hylophylax naevioides) chicks in soundproofed aviaries. Individuals were raised either in silence with no tutor or exposed to standardized playback of a heterospecific tutor. All individuals surviving to maturity took a minimum of 79 days to produce a crystallized version of adult song, which in all cases was indistinguishable from wild song types of their own species. These first insights into song development in tracheophone suboscines suggest that adult songs are innate rather than learnt. Given that empirical evidence for song learning in suboscines is restricted to polygamous and lek-mating species, whereas tracheophone suboscines are mainly monogamous with long-term social bonds, our results are consistent with the view that sexual selection promotes song learning in birds.